DISTINCTIVENESS OF DIALECT OF KARAKOL DISTRICT - F. J. Muradova (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about noticeable differences in the grammatical structure of dialects. In particular, the classification of adverbs used in the Karakol district dialect will be discussed.